Myocardial mechanical changes before and after bariatric surgery in individuals with obesity and diabetes: a 1-year follow-up study - Xiaoyan Kang; Linyan Zhou; Yanxia Zhang; Chunsong Kang; Jiping Xue (Scientific Reports)
Abstract Bariatric surgery may have an effect on myocardial mechanics in individuals with obesity and diabetes. In this study, two-dimensional speckle-tracking echocardiography was applied to evaluate the changes of left ventricular myocardial mechanics in individuals with obesity and diabetes before and after bariatric surgery. A total of 58 individuals with obesity were divided into an obesity-only group (30 patients) and an obesity + diabetes group (28 patients). Routine echocardiographic parameters and left ventricular global longitudinal strain (GLS) were compared between the two groups at baseline and 6 and 12 months postoperatively. At all three time points, GLS was lower in the obesity + diabetes group than in the obesity-only group. In both groups, the GLS increased successively at 6 and 12 months postoperatively. The change in GLS (∆GLS) from baseline to 6 months was higher than the △GLS from 6 to 12 months in both groups. The △GLS from baseline to 6 months was lower in the obesity + diabetes group than in the obesity-only group. Therefore, obese individuals can benefit from bariatric surgery, which includes improved heart function, delayed disease progression.